Evaluation of Acupuncture for Cancer Symptoms in a Cancer Institute in Brazil. Issue 1 (March 2013) - D'Alessandro, Eduardo; de Brito, Christina; Cecatto, Rebeca; Saul, Maira; Atta, Jose Antonio; Lin, Chin An
Introduction: Acupuncture has been progressively included in the practice of mainstream medicine in recent decades. The State of Sao Paulo Cancer Institute is a public hospital established in 2008 and its acupuncture service follows the experience and model of several oncology centres in the USA, aiming to optimise the treatment of symptoms such as postoperative pain, oncological pain, neuropathic pain, nausea, vomiting, xerostomia and fatigue induced by chemotherapy. This paper describes the population given acupuncture treatment and the effects of the intervention on symptom management. Methods: One hundred and eighty-three patients from our service were enrolled in the study. Baseline and final symptom intensity was recorded using a visual analogue score (VAS) ranging from 0 to 10 cm, with a higher score meaning higher symptom intensity. Results: Fifty-four (29.50%) were receiving active treatment with chemotherapy and/or radiotherapy, 29 (15.85%) were receiving hormone therapy and 100 (54.65%) were considered to be in remission. The main symptoms were: oncological pain in 44 (24.04%), chemotoxicity in 34 (18.6%), lumbar pain in 53 (28.96%) and chronic postoperative pain in 54 (28.4%). The mean (SD) initial symptom score was 7.04 (1.8), which was reduced to 2.56 (2.75) after treatment (p<0.001), an improvement of 63.6% in control of the symptoms. Further analysis of the data showed that the effect was similar in different indications for acupuncture treatment. Conclusions: Use of acupuncture may have improved symptom control in patients enrolled in this study.